Difusión espacial de la pobreza y destrucción del patrimonio natural: las dos caras de una misma moneda - Abaleron, Carlos Alberto (Revista EURE - Revista de Estudios Urbano Regionales, 1995)
Poverty is foisted off on the destruction of natural surroundings. This article attempts to demonstrate, by interpretation of the evolution in the space and times of San Carlos de Bariloche, Argentina, that that is no so, and that both are part of the negative effects of an urbanization process that obeys complex political, economic and cultural factors that externalize the costs of those factors that are physical and socially vulnerable. Í